Work ability index and perceived work ability as predictors of disability pension: a prospective study among Finnish municipal employees - Jääskeläinen, Anne; Kausto, Johanna; Seitsamo, Jorma; Ojajärvi, Anneli; Nygård, Clas-Håkan; Arjas, Elja; Leino-Arjas, Päivi (Scandinavian Journal of Work, Environment & Health, 2016)
' ' OBJECTIVES ': 'We analyzed the work ability index (WAI) and its first item (work ability score, WAS) – and subsequent four-year changes thereof – as predictors of disability pension (DP). ' ' METHODS ': 'We linked survey responses of 5251 Finnish municipal employees, aged 44–58 years, to pension and death register data until 2009. Job content (physical, mental, or mixed) was based on observation. Baseline (1981) WAI was divided into poor (<27), moderate (28–36), and good/excellent (>37) and WAS into poor (0–5), moderate (6–7), and good/excellent (8–10). Four-year changes in these scores were classified as strong decline (<lowest 15th percentile), slight decline, and no change/improved. Cox regression and receiver operating characteristic (ROC) analysis were used. ' ' RESULTS ': 'During follow-up, 2057 subjects were granted DP. Compared to those with good/excellent WAI, the hazard ratio (HR) for DP related to moderate and poor WAI, respectively, was 2.0 (95% CI 1.8–2.2) and 5.0 (95% CI 4.4–5.6), adjusted for sociodemographic variables and job content. For WAS, the HR were 1.8 (95% CI 1.6–2.0) and 3.4 (95% 3.0–3.8). Four-year decline in WAI/WAS further increased the risk. During the first four years of follow-up, the area under the curve (AUC) for WAI at cut-off point 27 was 0.66 (sensitivity 49.2% and specificity 82.9%) and 0.64 for cut-off point 36 (sensitivity 84.2% and specificity 44.3%). For WAS at cut-off point 5, the figures were AUC 0.63 (sensitivity 41.9% and specificity 85.0%) and AUC 0.65 for cut-off point 7 (sensitivity 78.2% and specificity 52.7%). ' ' CONCLUSION ': 'The single-item WAS can be considered a reasonable alternative to the seven-item WAI in describing the risk of DP and as a prognostic tool.
Keywords: disability pension; disability retirement; early retirement; Finland; Finnish municipal employee; perceived work ability; predictor; predictor of disability pension; prognostic risk marker; prognostic tool; prospective study; sensitivity; specificity; WAI; WAS; work ability; work ability index; work ability score